Pengaruh Kompensasi terhadap Kinerja Karyawan di PT. Panorama Alam Tropika Jakarta Selatan - Risma Arifin; Andi Rusdi Walinono; Ilyas Ilyas (Jurnal Manajemen Riset Inovasi, 2024)
The quality of human resources that has progressed can be caused by an increase in employee performance through the provision of appropriate compensation as remuneration to employees for the efforts they make for the company. In this era of globalization, companies are expected to be able to develop and experience changes for the better and earlier through employee work. One of the aims of this research is to determine the effect of compensation on employee performance at PT Panorama Alam Tropika, South Jakarta.The type of research used is a quantitative method with data collection techniques through distributing questionnaires to employees of PT Panorama Alam Tropika, South Jakarta. The population of this research is all employees of PT Panorama Alam Tropika, South Jakarta, with a sample of 13 employees.The analysis technique used in this research uses simple linear regression statistical analysis with the help of the SPSS version 23 application. And the results of this analysis can be interpreted to mean that compensation variables which include salaries, allowances, benefits and facilities have a significant influence on employee performance variables at PT Panorama Alam Tropika, South Jakarta. Coefficient of determination of compensation on employee performance at PT. The Tropical Natural Panorama of South Jakarta is 0.627 or 62.7%, while the remaining 37.3% is due to other factors outside the variables studied. The results of this research were obtained from the results of the t test (partial) which showed the calculated t value > t table (4,300 > 2.22814), with a significance of 0.001 < 0.05. This means that there is a significant positive influence of compensation on the performance of PT employees. Tropical Natural Panorama of South Jakarta.